CAT score single item analysis in patients with COPD: Results from COSYCONET - Siemens, Sarah Marietta von; Kauczor, Hans-Ulrich; Jobst, Bertram; Gogol, Manfred; Herth, Felix; Katus, Hugo (Respiratory medicine, 2019)
The COPD Assessment Test (CAT) is in widespread use for the evaluation of patients with chronic obstructive pulmonary disease (COPD). We assessed whether the CAT items carry additional information beyond the sum score regarding COPD characteristics including emphysema. Patients of GOLD grades 1 to 4 from the COPD cohort COSYCONET (German COPD and Systemic Consequences - Comorbidities Network) with complete CAT data were included (n=2270), of whom 493 had chest CT evaluated for the presence of emphysema. Comorbidities and lung function were assessed following standardised procedures. Cross-sectional data analysis was based on multiple regression analysis of the single CAT items against a panel of comorbidities, lung function, or CT characteristics (qualitative score, 15th percentile of mean lung density), with age, BMI and gender as covariates. This was supported by exploratory factor analysis. Regarding the relationship to comorbidities and emphysema, there were marked differences between CAT items, especially items 1 and 2 versus 3 to 8. This grouping was basically confirmed by factor analysis. Items 4 and 5, and to a lower degree 1, 2 and 6, appeared to be informative regarding the presence of emphysema, whereas the total score was not or less informative. Regarding comorbidities, similar findings as for the total CAT score were obtained for the modified Medical Research Council scale (mMRC) which was also informative regarding emphysema. Our findings suggest that the usefulness of the CAT can be increased if evaluated on the basis of single items which may be indicating the presence of comorbidities and emphysema.
Gesehen am 24.01.2020
For the COSYCONET study group: Andreas Stefan, Bals Robert, Behr Jürgen, Kahnert Kathrin, Bewig Burkhard, Buhl Roland, Ewert Ralf, Stubbe Beate, Joachim H. Ficker, Gogol Manfred, Grohé Christian, Hauck Rainer, Held Matthias, Jany Berthold, Henke Markus, Herth Felix, Höffken Gerd, A. Katus Hugo, Kirsten Anne-Marie, Watz Henrik, Koczulla Rembert, Kenn Klaus, Kronsbein Juliane, Kropf-Sanchen Cornelia, Lange Christoph, Zabel Peter, Pfeifer Michael, J. Randerath Winfried, Seeger Werner, Studnicka Michael, Taube Christian, Teschler Helmut, Timmermann Hartmut, Virchow J. Christian, Vogelmeier Claus, Wagner Ulrich, Welte Tobias, Wirtz Hubert
Names of participating study nurses: Doris Lehnert, Birte Struck, Lenka Krabbe, Barbara Arikan, Julia Tobias, Kornelia Speth, Jeanette Pieper, Margret Gleiniger, Britta Markworth, Zaklina Hinz, Ellen Burmann, Katrin Wons, Ulrike Rieber, Beate Schaufler, Katrin Schwedler, Sabine Michalewski, Sonja Rohweder, Patricia Berger, Diana Schottel, Vivien Janke, Rosalie Untsch, Jana Graf, Anita Reichel, Gertraud Weiß, Erich Traugott, Ilona Kietzmann, Michaela Schrade-Illmann, Beate Polte, Gudrun Hübner